Pemanfaatan Kapang Pelapuk Kayu (KPK) Indigenous Mycelioptora thermophilia KLUM1 Untuk Pengolahan Limbah Rumput Taman Sebagai Pakan Ternak - Ike Astiyandani; Evi Susanti (Universitas Negeri Malang, 2021)
Axonopus compressus as garden waste has the potential to become forage for livestock if it is processed by reducing its lignin content. Lignin is an anti-nutritional substance in animal feed whose presence can reduce the digestibility of feed nutrients. Mycelioptora thermophilia KLUM1 produces ligninase which can degrade lignin. The purpose of this study were to determine the effect of fermentation time and the number of spores of the Mycelioptora thermophilia KLUM1 on the levels of lignin, crude fat, and crude protein of Axonopus compressus. This research is a laboratory experimental study using a Completely Randomized Design (CRD) method, the first factor is fermentation time (14, and 21 days) and the second factor is the number of spores (1,72 x 107 , 4,29 x 107 , and 8,59 x 107 cells). The results showed that the best conditions for the levels of lignin and crude fat in this study were 8.59 x 107 cells for 21 days with a lignin content of 9.98% ± 0.23 and crude fat content of 3.43% ± 0 .04, while the best condition for crude protein content was 1.72 x 107 cells for 14 days of 11.64% ± 0.18.